(untitled) - Food and Agriculture Organization of the United Nations (Rome, 2008)
The designations employed and the presentation of material in this information product do not imply the espression of any opinion wwhatsoever on the part of the Food and Agriculture Oganization of the United Nations concerning the legal or development status of any country, territory, city or areas or of its authorities, or concerning the delimitation of its frontiers or boundaries.
Keywords: Fishery management,Coastal zone management,Quản lý nghề cá,Quản lý vùng ven biển